Medication administration errors made among undergraduate nursing students: A need for change in teaching methods - Schroers, Ginger; Ross, Jennifer Gunberg; Moriarty, Helene (Journal of professional nursing, 2022)
Systems factors, such as interruptions, contribute to nursing errors. Gaining an understanding of what contributes to nursing student errors can inform educational strategies aimed to improve patient safety. The aims of this study were to investigate: (a) within-subjects differences in error rates among nursing students during interrupted compared to uninterrupted simulated medication administration, (b) types of medication administration errors made by nursing students, and (c) nursing students' perceptions of their ability to independently administer medication. A descriptive comparative within-subjects design was utilized in this two-site study. Data on errors were collected via direct observation. Senior baccalaureate nursing student participants discussed their experience of interrupted and uninterrupted simulated medication administration during individual debriefing sessions. Nearly one-third of participants made errors. Error rates were similar in interrupted (19.4%) and uninterrupted (16.7%) conditions. Near-misses, which were not included in the error rates, were reported by 8% of participants. The most common error types were documentation and dose errors. Students attributed the interruption and lack of independent medication administration practice as causes for errors. Educational programs must adequately prepare nursing students for independent safe medication administration in complex work environments. The inclusion of systems factors in educational modalities is critical. •Nursing students preparing to graduate may not be ready for independent practice.•Nearly one-third of senior students made medication errors in a simulated scenario.•Students attributed interruptions and lack of independent practice to errors.•Systems factors, such as interruptions, are prevalent in healthcare environments.•Simulations with interruptions can offer safe realistic independent practice.